Current knowledge of Umbrian macrofungi (central Italy). (3rd September 2017) - Angelini, P.; Arcangeli, A.; Bistocchi, G.; Rubini, A.; Venanzoni, R.; Perini, C.
Abstract: An annotated checklist of 1016 species of fungi (Ascomycota and Basidiomycota), which have been recorded in 95 different localities, from 1990 to 2015, is presented for Umbria (Italy). The checklist was compiled from records of Umbrian fungi in scientific publications, unpublished lists and personal observations. This work represents the first comprehensive checklist of macrofungi for Umbria. Even if not complete, an exhaustive overview of the current knowledge of the mycobiota of Umbria is presented. Although a large amount of the regional territory has still to be explored for mycological diversity, this study offers an important support in compiling red-lists of endangered macrofungi, as well as to identify indicator species of particular habitats to be considered for wildlife reserves, as is currently done in many European countries.